Incidence and risk factors associated with atrioventricular block in the general population: the atherosclerosis risk in communities study and Cardiovascular Health Study - Zhang, Jingwei; Liu, Jia; Ye, Min; Zhang, Ming; Yao, Fengjuan; Cheng, Yunjiu (BMC cardiovascular disorders, 2024)
To identify risk factors correlated with atrioventricular block (AVB) in the general population. Participants in the Atherosclerosis Risk in Communities study (ARIC) and the Cardiovascular Health study (CHS) were enrolled. The presence of AVB was confirmed at an electrocardiogram (ECG) reading center using Minnesota ECG Classification. Cox proportional hazards models were performed to investigate potential risk factors of AVB, after adjustment for age, sex, race and traditional cardiovascular risk factors. During the 17 years of follow-up, a total of 731 high-degree AVB cases were identified. Age and sex-standardized rate of AVB was 2.79 and 2.35 per 1000 person-years in the white and the black population, respectively. With the increase of the geriatric population, the incidence of high-degree AVB will increase from 378,816 in 2020 to 535,076 in 2060, and most increment would occur among the elderly. Older age, male sex, the white race, overweight, comorbidities, declined forced vital capacity (FVC), elevated inflammation biomarkers, left bundle branch block and bifascicular block were independently associated with the incidence of high-degree AVB. To conclude, older age, male sex, white population, overweight, combined diabetes or chronic kidney disease, impaired FVC, elevated inflammation biomarkers, left bundle branch block and bifascicular block were independent predictors for high-degree AVB. The next 40 years would witness a dramatic increase in the incidence of high-degree AVB.